Bulgecin A as a β-lactam enhancer for carbapenem-resistant Pseudomonas aeruginosa and carbapenem-resistant Acinetobacter baumannii clinical isolates containing various resistance mechanisms - Skalweit MJ; Li M (Dove Medical Press, 2016)
Marion J Skalweit,1–5 Mei Li2 1Department of Medicine, 2Research Section, 3Infectious Diseases Section, Louis Stokes Cleveland Department of Veterans, 4Department of Medicine, 5Department of Biochemistry, Case Western Reserve University School of Medicine, Cleveland, OH, USA Abstract: Genetic screening of Pseudomonas aeruginosa (PSDA) and Acinetobacter baumannii (ACB) reveals genes that confer increased susceptibility to β-lactams when disrupted, suggesting novel drug targets. One such target is lytic transglycosylase. Bulgecin A (BlgA) is a natural product of Pseudomonas mesoacidophila and a lytic transglycosolase inhibitor that works synergistically with β-lactams targeting PBP3 for Enterobacteriaceae. BlgA also weakly inhibits di-Zn2+ metallo-β-lactamases like L1 of Stenotrophomonas maltophilia. We hypothesized that because of its unique mechanism of action, BlgA could restore susceptibility to carbapenems in carbapenem-resistant PSDA (CR-PSDA) and carbapenem-resistant ACB, as well as ACB resistant to sulbactam. A BlgA-containing extract was prepared using a previously published protocol. CR-PSDA clinical isolates demonstrating a variety of carbapenem resistance mechanisms (VIM-2 carbapenemases, efflux mechanisms, and AmpC producer expression) were characterized with agar dilution minimum inhibitory concentration (MIC) testing and polymerase chain reaction. Growth curves using these strains were prepared using meropenem, BlgA extract, and meropenem plus BlgA extract. A concentrated Blg A extract combined with low concentrations of meropenem, was able to inhibit the growth of clinical strains of CR-PSDA for strains that had meropenem MICs ≥8 mg/L by agar dilution, and a clinical strain of an OXA-24 producing ACB that had a meropenem MIC >32 mg/L and intermediate ampicillin/sulbactam susceptibility. Similar experiments were conducted on a TEM-1 producing ACB strain resistant to sulbactam. BlgA with ampicillin/sulbactam inhibited the growth of this organism. As in Enterobacteriaceae, BlgA appears to restore the efficacy of meropenem in suppressing the growth of CR-PSDA and carbapenem-resistant ACB strains with a variety of common carbapenem resistance mechanisms. BlgA extract also inhibits VIM-2 β-lactamase in vitro. BlgA may prove to be an exciting adjunctive compound to extend the life of carbapenems against these vexing pathogens. Keywords: carbapenem resistance, metallo-β-lactamase, efflux pumps